Visualization in the writing process: a case study of struggling K-4 learners in a summer writing camp - Jurand, Erin K. (Kansas State University, 2008)
The No Child Left Behind Act of 2001 (PL 107-110) drives today's teaching environment. With the pressure not to leave any student behind, classroom teachers often request struggling students to attend summer school. This qualitative case study sought to gain a deeper understanding of how visualization embedded in the writing process may influence struggling learners in a kindergarten through fourth grade summer writing camp. The 3 1/2 week summer writing camp was based on Donald Graves' (1983/2003) writer's workshop and writing process. The selected 19 students (K - 4) and 5 teachers in a Midwestern school district participated in the visual, learning, and literacy-rich environment. During the writing workshop, teachers gave Lucy Calkin's (1994) inspired mini-lessons to teach struggling students how to use visualization embedded in the writing process. Students participated in 4 community-based field experiences, which served as inspiration for drawing and writing. Mental imagery has powerful effects on reading comprehension (Sadoski, 1983, 1985) and students recalled information and images from the field experiences by observing digital photographs, and then drawing and writing. Thirty-nine student art/writing samples were analyzed using Lowenfeld and Brittain's (1975) stages of artistic development, Northwest Regional Educational Laboratory (2004) writing levels, and Piaget and Inhelder's (1969/2000) stages of cognitive development. Drawing in the writing process created tangible images to help student authors in the primary grades increase their Six-Trait Analytical (Spandel, 2004) writing scores for Ideas, Organization, and Conventions. Students in the intermediate writing group also increased their writing scores in Ideas, Voice, and Conventions. In addition, the data revealed the student's stage of artistic development reflects his or her writing level and stage of cognitive development. The involved teachers believed aspects of the summer writing camp could be incorporated throughout the school year, and they wanted to learn more about using visualization in the writing process. This study provided insight essential to better understand how visualization embedded in the writing process influences struggling learners.
Keywords: visualization; writing process; six-trait; artistic development; cognitive development; summer school; Education, Curriculum and Instruction (0727); Education, Elementary (0524)